Analisis Praktik Klinik Keperawatan Pada Pasien Stroke Non Hemoragik dengan Pemberian Latihan Pemasangan Puzzle Jigsaw Terhadap Peningkatan Kekuatan Otot Ekstermitas Atas Rsud Prof. Dr. H. Aloei Saboe Kota Gorontalo - Fadli Syamsuddin; Riyana Nur Ridwan Adam (Pusat Riset dan Inovasi Nasional, 2023)
Stroke is an acute neurological condition caused by decreased blood flow to the brain. Nervous system dysfunction occurs suddenly (within seconds) or rapidly (within hours) and the symptoms and signs correspond to the local area of ​​the brain affected. Objective: To conduct an analysis of managed cases with a medical diagnosis of non-hemorrhagic stroke with jigsaw puzzle pairing exercise therapy to increase upper extremity muscle strength Methods: This research is a quasi-experimental design with pre and post test. This type of research is a research design that is used to look for causal relationships with research involvement. The sample used in this study were 6 patients with a critical sample of patients who had non-hemorrhagic stroke who were treated at Prof. Hospital. Dr. Aloei Saboe Gorontalo City. Results: The results of the study showed that changes in muscle strength were only present in Mr. I.T obtained an increase on the evaluation of the third day of implementation where there was an increase in muscle strength to 5/4, which means there was an increase using the MMAS (Modified Muscle Assessment Scale) it was found that the client was only able to lift the top part of the puzzle and put it back. (The patient reaches forward at arm's length, lifts the top of the puzzle, releases it back to the part of the table that is closest to the patient's body). Conclusion: Based on the research conducted, it was found that 6 respondents from the results of the assessment had measuring results that had been carried out after the Jigsaw Puzzle installation exercise, it was found that there was a change in the range of motion of the client's fingers while for the client's muscle strength and fine motor movements there had been no change. Stroke attack can cause permanent physical disability.